SPE Eastern Regional Meeting 2013
DOI: 10.2118/165672-ms
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effect of Drilling Azimuth in Shale Gas Reservoirs

Abstract: With the advent of horizontal drilling and fracturing low-permeability reservoirs to produce hydrocarbons, it has become common practice within most fields to drill wells in the direction of minimum horizontal stress in a normal stress region to maximize production and minimize drilling risk. The primary reason for this is that induced fractures tend to propagate along the plane containing the intermediate and maximum stresses (typically overburden and maximum horizontal stresses in a normally stressed region)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The results demonstrated that transverse fractured horizontal wells outperformed all other well azimuths in the Marcellus formation. In fact, it was shown that the more the horizontal wellbore deviated from minimum horizontal stress r Hmin , the lower the estimated ultimate recovery (EUR) (Zinn et al 2011). Wutherick et al (2013) studied further the impact of well azimuth and explained the conclusions made in the Marcellus Formation by Zinn et al with a simple geometry to illustrate the stimulated reservoir volume (SRV) at varied well azimuths.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that transverse fractured horizontal wells outperformed all other well azimuths in the Marcellus formation. In fact, it was shown that the more the horizontal wellbore deviated from minimum horizontal stress r Hmin , the lower the estimated ultimate recovery (EUR) (Zinn et al 2011). Wutherick et al (2013) studied further the impact of well azimuth and explained the conclusions made in the Marcellus Formation by Zinn et al with a simple geometry to illustrate the stimulated reservoir volume (SRV) at varied well azimuths.…”
Section: Introductionmentioning
confidence: 99%